The promotive relationship between personality and self-reported offending - Jolliffe, Darrick (Psychology, crime & law, 2024)
Research has regularly linked the five-factor model (FFM) or ‘Big Five’ personality model to behaviours, including antisocial behaviour and offending. Three of the five factors, namely, low agreeableness, low conscientiousness and high neuroticism, have consistently been identified as important for explaining offending of males and females. These conclusions have generally been based on considering the FFM as linearly related to offending, when the factors of the FFM could act as ‘risk’ factors (those with extreme negative scores having an increased likelihood of offending) or as ‘promotive’ factors (those with extreme positive scores having a decreased likelihood of offending). In this research the effects of the risk and promotive factors of the FFM on self-reported offending of the male and female children of the Cambridge Study in Delinquent Development (CSDD) were examined. The results suggested that many of the factors of the FFM were better considered as promotive factors as opposed to risk factors or mixed (linearly related), and that promotive factors independently predicted offending after controlling for parental, social, socioeconomic and school factors. Limitations, directions for future research, and implications for interventions to reduce offending are discussed.